Thermoanalytical study and characterization of native starches of Paraná pine seeds (Araucaria angustiofolia, Bert O. Ktze) and European chestnut seeds (Castanea sativa, Mill) - Bicudo, S. C. W.; Demiate, I. M.; Bannach, G.; Lacerda, L. G.; Carvalho Filho, M. A. S.; Ionashiro, Massao [UNESP]; Schnitzler, E. (Editora Unesp, 2009)
O amido é o mais importante carboidrato de reserva em plantas. É uma matéria-prima originária de diversas fontes botânicas, e muito usado nas indústrias de alimentos, papéis, químicas, farmacêuticas, têxteis e outras. Neste trabalho, amidos nativos das sementes de pinheiro do Paraná (pinhão) (Araucaria angustiofolia, Bert O. Ktze) e de castanha Européia (Castanea sativa, Mill) foram estudados pelas técnicas termoanalíticas: termogravimetria (TG), análise térmica diferencial (DTA) e calorimetria exploratória diferencial (DSC), bem como difratometria de raios-X. Também os teores de amilose aparente e total foram determinados.

Starch is the most important carbohydrate storage in plants. It is a raw material with diverse botanical origins, and is used by the food, paper, chemical, pharmaceutical, textile and other industries. In this work, native starches of Paraná pine seeds (pinhão) (Araucária angustiofolia, Bert O. Ktze) and european chestnut seeds (Castanea sativa, Mill) were studied by thermoanalytical techniques: thermo-gravimetry (TG), differential thermal analysis (DTA) and differential scanning calorimetry (DSC), as well as X-ray powder patterns diffractometry. Apparent and total amylose content was also determined.
Estudo termoanalítico e caracterização de amidos nativos de sementes do pinheiro do Paraná (Araucária angustiofolia, Bert O. Ktze) e sementes de castanha européia (Castanea saliva, Mill)
Keywords: Amidos; gelatinização; análise térmica; entalpia; Starch; gelatinization; thermal analysis; enthalpy